2007
DOI: 10.1002/bmc.781
|View full text |Cite
|
Sign up to set email alerts
|

Permeability of atenolol and propranolol in the presence of dimethyl sulfoxide in rat single‐pass intestinal perfusion assay with liquid chromatography/UV detection

Abstract: A simple and sensitive RP-HPLC-UV method was developed and validated for simultaneous determination of atenolol and propranolol and subsequently applied to investigate the effect of dimethyl sulfoxide in rat in situ intestinal permeability studies. Atenolol (400 microm) and propranolol (100 microm) were perfused in the small intestine of anaesthetized (pentobarbitone sodium 60 mg/kg, i.p.) male Sprague-Dawley rats either in the presence (1, 3 and 5%) or in the absence of dimethyl sulfoxide. There was no signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 18 publications
2
9
0
Order By: Relevance
“…To determine the reason for the higher exposure of DNJ in rats after administration of SZ–A, the intestinal absorption of the components was investigated through in situ single-pass intestinal perfusion of SZ–A (21.73 μg/mL, containing 50 μM DNJ, 9.5 μM FGM, 7.8 μM DAB) and purified DNJ (50 μM). Here, the P lumen of propranolol and atenolol agreed with previous values obtained in single-pass intestinal perfusion in rats [ 15 ], which suggested that the assay was reliable. The cumulative amount of three alkaloids in mesenteric plasma was increased time–dependently ( Figure 3 ), suggesting that three compounds could be absorbed into blood through the intestinal barrier.…”
Section: Resultssupporting
confidence: 89%
“…To determine the reason for the higher exposure of DNJ in rats after administration of SZ–A, the intestinal absorption of the components was investigated through in situ single-pass intestinal perfusion of SZ–A (21.73 μg/mL, containing 50 μM DNJ, 9.5 μM FGM, 7.8 μM DAB) and purified DNJ (50 μM). Here, the P lumen of propranolol and atenolol agreed with previous values obtained in single-pass intestinal perfusion in rats [ 15 ], which suggested that the assay was reliable. The cumulative amount of three alkaloids in mesenteric plasma was increased time–dependently ( Figure 3 ), suggesting that three compounds could be absorbed into blood through the intestinal barrier.…”
Section: Resultssupporting
confidence: 89%
“…The P eff values obtained after co-perfusion of markers are in the well agreement in comparison to the permeabilities of the marker compounds perfused alone and the previously reported values [1,4,8,[10][11][12][13][14][15][16][17][18][19][20][21][22]. This indicates that permeability of these compounds is not much affected in the presence of each other.…”
Section: Application Of the Methods For In Situ Permeability Studysupporting
confidence: 86%
“…Atenolol, metoprolol, ketoprofen, and enalaprilat were added from DMSO stock solutions to the donor chamber medium (mucosal side) to achieve a final concentration of 25 μM for each drug. The final concentration of DMSO never exceeded 0.5% (w/w), which has been validated previously with respect to intestinal tissue integrity …”
Section: Methodsmentioning
confidence: 53%